2018
DOI: 10.1007/s11695-018-3239-3
|View full text |Cite
|
Sign up to set email alerts
|

A Prospective Randomized Controlled Trial of the Metabolic Effects of Sleeve Gastrectomy with Transit Bipartition

Abstract: SG + TB is superior to SMT and was associated with a better metabolic and cardiovascular profile.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
18
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(18 citation statements)
references
References 28 publications
0
18
0
Order By: Relevance
“…In a 2018, 24-month, parallel-group, randomized controlled trial (RCT) of the metabolic effects of SG-TB, 20 low-BMI patients with T2DM were randomized to SG-TB or standard medical therapy. At 24 months, HbA 1C was statistically significantly reduced from baseline in the SG-TB group (9.3 ± 2.1 vs 5.5 ± 1.1%, p < 0.05) relative to the medical therapy group (8.0 ± 1.5 vs 8.3 ± 1.1%, p = NS) [70].…”
Section: Indications/contraindications Weight Loss Diabetesmentioning
confidence: 82%
See 1 more Smart Citation
“…In a 2018, 24-month, parallel-group, randomized controlled trial (RCT) of the metabolic effects of SG-TB, 20 low-BMI patients with T2DM were randomized to SG-TB or standard medical therapy. At 24 months, HbA 1C was statistically significantly reduced from baseline in the SG-TB group (9.3 ± 2.1 vs 5.5 ± 1.1%, p < 0.05) relative to the medical therapy group (8.0 ± 1.5 vs 8.3 ± 1.1%, p = NS) [70].…”
Section: Indications/contraindications Weight Loss Diabetesmentioning
confidence: 82%
“…The procedure has no narrow anastomoses, excluded segments, or prostheses [68,69]. SG-TB employs the principle of functional restriction, defined by Santoro et al as a metabolically (rather than mechanically/ physically) driven rate of reduction in gastric emptying and intestinal transit [70].…”
Section: Sleeve Gastrectomy With Duodenojejunal Bypass (Fig 6)mentioning
confidence: 99%
“…The metabolic impact of BS on the reduction of cardiovascular risk factors and the prevention of these factors has been documented in several studies [38,74,75,76]. A meta-analysis of the long-term effect of BS, DM, and hypertension showed that the risk decreased after BS, with relative risks of 0.33 (95% CI = 0.26–0.41; I 2 = 42%), 0.54 (95% CI = 0.46–0.64, I 2 = 68%), and 0.33 (95% CI = 0.22–0.46, I 2 = 74%).…”
Section: Discussionmentioning
confidence: 99%
“…The authors searched MEDLINE (via EBSCO), Scopus, and Web of Science databases between 1990 and 2009 and found 15 eligible studies that have investigated the effect of different types of bariatric surgery (BS) on fasting levels of FGF-19, while our initial search represents that at least eight eligible studies have been missed in the evidence synthesis. [2][3][4][5][6][7][8][9] Ignoring such a large number of eligible studies may lead to ambiguous findings since the inclusion of eligible studies might substantially change the overall effects. After a careful review, we noticed that the authors used a narrowed search strategy with a limited number of related keywords.…”
mentioning
confidence: 99%